Timing of prenatal exposure to trauma and altered placental expressions of hypothalamic‐pituitary‐adrenal axis genes and genes driving neurodevelopment. (19th April 2018) - Zhang, W.; Li, Q.; Deyssenroth, M.; Lambertini, L.; Finik, J.; Ham, J.; Huang, Y.; Tsuchiya, K. J.; Pehme, P.; Buthmann, J.; Yoshida, S.; Chen, J.; et al.
Abstract : Prenatal maternal stress increases the risk for negative developmental outcomes in offspring; however, the underlying biological mechanisms remain largely unexplored. In the present study, alterations in placental gene expression associated with maternal stress were examined to clarify the potential underlying epi/genetic mechanisms. Expression levels of 40 selected genes involved in regulating foetal hypothalamic‐pituitary‐adrenal axis and neurodevelopment were profiled in placental tissues collected from a birth cohort established around the time of Superstorm Sandy. Objective prenatal traumatic stress was defined as whether mothers were exposed to Superstorm Sandy during pregnancy. Among the 275 mother‐infant dyads, 181 dyads were delivered before Superstorm Sandy (ie, Control), 66 dyads were exposed to Superstorm Sandy during the first trimester (ie, Early Exposure) and 28 were exposed to Superstorm Sandy during the second or third trimester (ie, Mid‐Late Exposure). Across all trimesters, expression of HSD11B2, MAOA, ZNF507 and DYRK1A was down‐regulated among those exposed to Superstorm Sandy during pregnancy. Furthermore, trimester‐specific differences were also observed: exposure during early gestation was associated with down‐regulation of HSD11B1 and MAOB and up‐regulation of CRHBP ; exposure during mid‐late gestation was associated with up‐regulation of SRD5A3 . The findings of the present study suggest that placental gene expression may be altered in response to traumatic stress exposure during pregnancy, and the susceptibility of these genes is dependent on the time of the exposure during pregnancy. Further studies should aim to clarify the biological mechanisms that underlie trimester‐specific exposure by evaluating the differential impact on offspring neurodevelopment later in childhood.